Androgen receptor expression in triple negative breast cancer: an Algerian population study - Amel Hedjem; Amal Kouchkar; Amel Ladjeroud; Nacera Zerrouki; Fatima Benaissa; Nasir A. Ibrahim; Mohammed Saad Aleissa; Nosiba S. Basher; Assia Derguini; Takfarinas Idres; Karim Houali (Libyan Journal of Medicine, 2025)
Triple-negative breast cancer (TNBC) is a molecular subtype of breast cancer characterized by the absence of estrogen and progesterone receptors and the lack of HER2 overexpression. TNBC is highly heterogeneous, complicating the identification of new therapeutic targets. However, the expression of the androgen receptor (AR) in the luminal androgen receptor (LAR TNBC) subgroup has opened the door to alternative therapeutic approaches. This study aimed to assess AR expression and correlate it with clinicopathological factors in 160 early-stage TNBC patients treated from February 2015 to February 2017. Our findings reveal that AR expression is observed in 16.87% (27/160) of ≥1% AR positivity cases. Moreover, a significant 12.5% (20/160) was found in ≥10% AR positive cases. Positive AR expression was inversely correlated with a high Ki-67 proliferation index and with the basal immunophenotype. The five-year survival rate for our cohort was 83.12%, and no significant association between AR expression and overall survival was observed (p = 0.77). The study highlights the potential role of AR expression in TNBC and its implications for therapeutic strategies, although no significant association with overall survival was found.